Teach yourself to meditate : over 20 simple exercises for peace, health and clarity of mind - Harrison, Eric (Judy Piatkus LondonGB, 1994)
Explains what meditation is, why persons meditate, and expected benefits of meditation. Outlines 10 basic techniques including: focusing, being in touch with reality, naming, and clearing. Explains how to integrate meditation into daily life.